Performance and home advantage in handball - Pic, M. (Journal of Human Kinetics, 2018)
The main objective of this research was to delve into the concept of playing handball at home from a classical perspective of previous studies. The emergence of regularities or certain patterns of play can be explained by the location of matches. Through an observational methodology and a nomothetic, monitoring and multidimensional design, thirtynine European elite handball matches were selected (N = 39). A mixed 'ad hoc' registration system was designed. Records were made of the last three minutes of home and visiting games of which images were available. Two observers with observational methodology experience participated in the study. The quality of the records was dealt with in an intraobserver and interobserver way. Two different techniques were applied for the treatment of the data: a) detection of behavioral patterns by Theme (p < .005) (Magnusson, 2000) and b) Chaid decision trees (p < .05) using SPSSv.24. The results showed the existence of T-patterns according to the location (different T-patterns: home: 1085; away: 1242) of the matches. The categories most involved in effective launches were unveiled. On the other hand, the Chaid model also showed the effect of location (p < .001): home-win (node 9) (n = 149, 69%), away-win (node 10) (n = 15, 16%) in handball. Crossing analysis offered enriched interpretations to advance in the home advantage concept. From this study, guidelines can be drawn that may help handball coaches to build training tasks as differences in behavioral patterns between home or away play in handball were identified. Thus, designing tasks considering a match location has requires specificity.